Terahertz quantum cascade lasers with >1 W output powers - Li, Lianhe; Chen, Li; Zhu, Jingxuan; Freeman, J; Dean, P; Valavanis, A; Davies, A.G; Linfield, E.H (Electronics letters, 2014)
Terahertz (THz) frequency quantum cascade lasers emitting peak powers of >1 W from a single facet in the pulsed mode are demonstrated. The active region is based on a bound-to-continuum transition with a one-well injector, and is embedded into a surface-plasmon waveguide. The lasers emit at a frequency of ∼3.4 THz and have a maximum operating temperature of 123 K. The maximum measured emitted powers are ∼1.01 W at 10 K and ∼420 mW at 77 K, with no correction made to allow for the optical collection efficiency of the apparatus.